Opinion changes among participants in citizen participation workshops: a case study on the final disposal of removed soil outside Fukushima Prefecture - Shibata, Yukihide; Cui, Qinglin; Souma, Yume; Tsujimoto, Mie; Ue, Honami; Kihara, Nana; Takamoto, Maiko; Yasutaka, Tetsuo; Ohnuma, Susumu (Frontiers in Environmental Science, 2025)
Existing studies on risk perception have identified key factors influencing policymaking and its support; however, their effects in practical situations remain unclear. While research on science and technology communication has explored various case studies, the measurement of changes in participants’ opinions regarding risk perception and its related factors has been rare. This study seeks to integrate these two research areas by examining participants’ opinion changes during a practical setting—workshops on the final disposal of removed soil outside Fukushima Prefecture. Specifically, the study investigates changes in psychological variables, such as policy acceptance and risk perception. To achieve this, pre- and post-workshop questionnaire surveys were issued to 47 participants to assess identify the factors expected to correlate with acceptance and risk perception. The results revealed significant differences in participants’ interest, sense of involvement, knowledge, risk perception, and certain acceptance aspects before and after the workshops. Furthermore, significant correlations were found between acceptance, risk perception, interest, and trust. Notably, participants’ interests and perceptions of their involvement were significantly correlated only after the workshops. Therefore, this study contributes to the literature by presenting a concrete yet nuanced case in environmental risk psychology, thus helping integrate studies on citizen participation with science and technology communication.